An Event Announcer System - Mun, Leong Kar; Mohamad Mohsin, Mohamad Farhan (Multidisciplinary Applied Research and Innovation, 2023)
Nowadays, most event organizers use social media platforms such as Facebook, WhatsApp, and Telegram to disseminate event information. However, because they do not follow or subscribe to the event page or group, this is not an effective platform for event advertising. Aside from that, registering for the event via Google Form is inefficient for participants because the link to the registration page is pushed to the bottom when new messages are added to the page. Furthermore, participant management is difficult for the event manager to manage. As a result, this study developed an Event Announcer System, a mobile application that can help potential participants in finding information about upcoming events and registering for them. This application can also assist the event manager in advertising new events and managing registration efficiently. The rapid application development methodology was used to create this system. The functional requirements were first gathered via interviews and content analysis. Then, based on the requirements gathered, a prototype called event announcer system was created, and a field study was conducted to evaluate the prototype's usability. With 98% satisfaction, the evaluation results show that this system is useful and simple to use. The respondents were also satisfied with the functionality offered by this system.